2016
DOI: 10.1017/s1478951516000055
|View full text |Cite
|
Sign up to set email alerts
|

When cancer cannot be cured: A qualitative study on relationship changes in couples facing advanced melanoma

Abstract: Our findings revealed a differentiated and complex picture about relationship changes over time, which also might aid in the development of support programs for couples dealing with advanced cancer, focusing on the aspects of caring, closeness/distance regulation, and communication patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…While this study was being planned, only two studies were found which had the specific objective of exploring experiences and needs in family relationships in cases of cancer in the palliative phase (Badr & Taylor, 2006;Gardner, 2008). When the study was being summarised, a further three studies had been added (Drabe et al, 2016;Fergus & Gray, 2009;Møllerberg et al, 2017). Because few studies were found with the specific objective of exploring experiences and needs in family relationships, studies with other objectives were also included (e.g.…”
Section: Family Relationships During Cancer In the Palliative Phasementioning
confidence: 99%
See 3 more Smart Citations
“…While this study was being planned, only two studies were found which had the specific objective of exploring experiences and needs in family relationships in cases of cancer in the palliative phase (Badr & Taylor, 2006;Gardner, 2008). When the study was being summarised, a further three studies had been added (Drabe et al, 2016;Fergus & Gray, 2009;Møllerberg et al, 2017). Because few studies were found with the specific objective of exploring experiences and needs in family relationships, studies with other objectives were also included (e.g.…”
Section: Family Relationships During Cancer In the Palliative Phasementioning
confidence: 99%
“…W. Robinson et al, 2005). Badr & Taylor (2006) (Drabe et al, 2016;Gardner, 2008;Møllerberg et al, 2017). Patients in the other studies were in both the curative and palliative phases (Badr & Taylor, 2006;Fergus & Gray, 2009).…”
Section: Family Relationships During Cancer In the Palliative Phasementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, having a meaningful, intimate relationship during incurable illness is an important protective factor for individual well-being of both patients and partners (Hagedoorn, Sanderman, Bolks, Tuinstra, & Coyne, 2008; Li & Loke, 2014; Lyons, Miller, & McCarthy, 2016; Rodin et al, 2007). An incurable stage of illness may, however, also bring profound relationship challenges for couples, such as negotiating difficult choices regarding end-of-life care, coping with anticipatory grief, role and lifestyle changes, talking about the ill partner’s legacy in psychological and practical matters, or even trying to resolve long-standing conflicts (Drabe et al, 2016; Manne & Badr, 2008; Taylor, 2014; Tie & Poulsen, 2013). Some couples’ relationship even risks deterioration in this phase of life (Koop & Strang, 2003; Weingarten, 2013).…”
mentioning
confidence: 99%